Efeitos da carga hidráulica, da profundidade de instalação do cilindro interno e do diâmetro do cilindro externo na determinação da velocidade de infiltração básica pelo infiltrômetro de anel - de Oliveira , Sizernando Luiz; Bernardo , Salassier; Martyn , Peter John; Condé, Alcides R; Sediyama, Gilberto C (Revista Ceres, 2025)
The effects of the hydraulic head and installation depth of the inner cylinder and diameter of the outer cylinder in determining the basic infiltration rate for the ring infiltrometer were studied. Work was carried out in podzolic soil at the hydraulic laboratory of the Federal University of Viçosa, Viçosa, Minas Gerais, Brazil.